Estimation of RF and ELF dose by anatomical location in the brain from wireless phones in the MOBI-Kids study. (May 2022) - Calderón, Carolina; Castaño-Vinyals, Gemma; Maslanyj, Myron; Wiart, Joe; Lee, Ae-Kyoung; Taki, Masao; Wake, Kanako; Abert, Alex; Badia, Francesc; Hadjem, Abdelhamid; Kromhout, Hans; de Llobet, Patricia; et al.
Graphical abstract: Highlights: Epidemiological studies on mobile phone radiation typically rely on phone use history. MOBI-Kids is the first study to estimate RF and ELF dose from wireless phones. RF and ELF doses vary by age, phone model, communication system and amount of use. Communication system and location in the brain are key determinants of dose. Duration and number of calls are likely to be crude proxies of dose. Abstract: Wireless phones (both mobile and cordless) emit not only radiofrequency (RF) electromagnetic fields (EMF) but also extremely low frequency (ELF) magnetic fields, both of which should be considered in epidemiological studies of the possible adverse health effects of use of such devices. This paper describes a unique algorithm, developed for the multinational case-control MOBI-Kids study, that estimates the cumulative specific energy (CSE) and the cumulative induced current density (CICD) in the brain from RF and ELF fields, respectively, for each subject in the study (aged 10–24 years old). Factors such as age, tumour location, self-reported phone models and usage patterns (laterality, call frequency/duration and hands-free use) were considered, as was the prevalence of different communication systems over time. Median CSE and CICD were substantially higher in GSM than 3G systems and varied considerably with location in the brain. Agreement between RF CSE and mobile phone use variables was moderate to null, depending on the communication system. Agreement between mobile phone use variables and ELF CICD was higher overall but also strongly dependent on communication system. Despite ELF dose distribution across the brain being more diffuse than that of RF, high correlation was observed between RF and ELF dose. The algorithm was used to systematically estimate the localised RF and ELF doses in the brain from wireless phones, which were found to be strongly dependent on location and communication system. Analysis of cartographies showed high correlation across phone models and across ages, however diagonal agreement between these cartographies suggest these factors do affect dose distribution to some level. Overall, duration and number of calls may not be adequate proxies of dose, particularly as communication systems available for voice calls tend to become more complex with time.